Intralocus sexual conflict and offspring sex ratio - Masako Katsuki; Tomohiro Harano; Takahisa Miyatake; Kensuke Okada; David J. Hosken (Ecology Letters, 2012)
Ecology Letters (2012) Abstract Males and females frequently have different fitness optima for shared traits, and as a result, genotypes that are high fitness as males are low fitness as females, and vice versa . When this occurs, biasing of offspring sex‐ratio to reduce the production of the lower‐fitness sex would be advantageous, so that for example, broods produced by high‐fitness females should contain fewer sons. We tested for offspring sex‐ratio biasing consistent with these predictions in broad‐horned flour beetles. We found that in both wild‐type beetles and populations subject to artificial selection for high‐ and low‐fitness males, offspring sex ratios were biased in the predicted direction: low‐fitness females produced an excess of sons, whereas high‐fitness females produced an excess of daughters. Thus, these beetles are able to adaptively bias sex ratio and recoup indirect fitness benefits of mate choice.